2004
DOI: 10.1200/jco.2004.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Trastuzumab Followed by Weekly Paclitaxel/Carboplatin As First-Line Treatment for Patients With Metastatic Breast Cancer

Abstract: This trial confirms the activity and tolerability of weekly paclitaxel/carboplatin alone or in combination with trastuzumab in women with HER-2 overexpressing metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 17 publications
3
35
0
1
Order By: Relevance
“…7A and 8A). This finding correspond well with the result that 60-70% metastatic patients with HER-2-positive tumors appear intrinsically resistant to trastuzumab as a sole therapy (30,31). Furthermore, trastuzumab alone or in combination with docetaxel or PTX was not effective in clinical trials for HER-2-positive prostate tumors (32,33).…”
Section: Discussionsupporting
confidence: 84%
“…7A and 8A). This finding correspond well with the result that 60-70% metastatic patients with HER-2-positive tumors appear intrinsically resistant to trastuzumab as a sole therapy (30,31). Furthermore, trastuzumab alone or in combination with docetaxel or PTX was not effective in clinical trials for HER-2-positive prostate tumors (32,33).…”
Section: Discussionsupporting
confidence: 84%
“…Preoperative chemotherapy for HER2-negative tumors employed one of the following regimens: AC (six cycles of doxorubicin 60 mg/m 2 and cyclophosphamide 600 mg/m 2 , q 3 weeks); dose dense (dd) AC (AC q 2 weeks with filgrastim) [11]; AD (six cycles of doxorubicin 50 mg/m 2 and docetaxel 75 mg/m 2 ) or DC (six cycles of docetaxel 75 mg/m 2 and capecitabine 2 9 dd 1,000 mg/m 2 orally during 14 days, q 3 weeks) [12,13]. For HER2-positive tumors, the regimens included ddAC and PTC (paclitaxel 80 mg/m 2 week -1 , trastuzumab 2 mg/kg and carboplatin AUC 2-3 mg/ml min times 6, q 8 weeks) after 2005 [14,15]. After one or three cycles (depending on the specific protocol) the tumor response was evaluated by contrast enhanced MRI [16].…”
Section: Clinicopathological Datamentioning
confidence: 99%
“…Both trials confirmed that both regimens are active against MBC with tolerable side effects [166]. Other groups showed that the combination of cisplatin/carboplatin with docetaxel/paclitaxel and trastuzumab as first-line therapy in patients with MBC overexpressing HER2/neu is promising (RR up to 80%), with tolerable toxicities [167,168,169,170,171]. An added advantage in terms of RR was also noted when trastuzumab was added to the carboplatin/cisplatin and gemcitabine combination for first-line therapy of MBC patients overexpressing HER2/neu [172,173,174].…”
Section: Experience With Targeted Therapymentioning
confidence: 78%